A Shift From Logistic Software to Service Model: A Case Study of New Service-Driven-Software for Management of Emergency Supplies During Disasters and Emergency Conditions by WHO - Rasheed, Huma; Usman, Muhammad; Ahmed, Waqas; Bacha, Muhammad Haroon; Zafar, Aliya; Bukhari, Khalid Saeed (Frontiers in Pharmacology, 2019)
World Health Organization (WHO) states access to medicine as a priority area for universal health coverage, wherein a well-functioning medicine supply chain is indispensable. Optimization of supply chains to cut losses related to overstocking, expiration, and inefficiencies protect the investments and strengthen health systems to better deliver the health services. This article shares the experience of developing a service-driven-software for pharmaceutical supplies during emergency conditions and disasters, the advantages gained, and the feed-back from different countries. In 2005, Logistic Support System (LSS), the updated version of SUMA (Supply Management), was introduced by WHO during the earthquake in Pakistan which had offered valuable but limited services to many countries. Moving from ad hoc to a more organized approach, the medical donations and stockpiles of essential medicinal supplies were inventoried on LSS database for managing the dispatch of medical supplies to the disaster-hit area in a shortest possible time. Post disaster rescue and rehabilitation work further instigated the need for development of a new software, Pharmaceutical Information Management System (PIMS), that was effective in the emergency as well as routine inventory operations. It was used for efficient and improved access of medicines and faster decision making. The new systems proved vital to anticipate over/under stocking through proactive alerts and prompting. The updated information on epidemiological and drug utilization needs were crucial for the effective quantification and ordering throughout the supply chain. Implementation of PIMS demanded appreciable customization including conversion of system from stand-alone to online system with consolidation of information on stocks from all locations. Provision of multiuser option allowed facilitation according to the user authorization, and was equipped with improved-speed, efficiency, and security. PIMS was successfully replicated by the pioneer team of pharmacist from Pakistan in other countries.